Comparative Genetic Structure of Cannabis sativa Including Federally Produced, Wild Collected, and Cultivated Samples - Schwabe, Anna L.; Hansen, Connor J.; Hyslop, Richard M.; McGlaughlin, Mitchell E. (Frontiers in Plant Science, 2021)
Currently in the U.S. the sole licensed facility to cultivate Cannabis sativa L. for research purposes is the University of Mississippi, which is funded by the National Institute on Drug Abuse (NIDA). Studies researching Cannabis flower consumption rely on NIDA-supplied “research grade marijuana”. Previous research found that cannabinoid levels of NIDA supplied Cannabis do not align with commercially available Cannabis. We sought to investigate the genetic identity of Cannabis supplied by NIDA relative to common categories within the species. This is the first genetic study to include “research grade marijuana” from NIDA. Samples (49) were assigned as Wild Hemp (feral;6) and Cultivated Hemp (3), NIDA (2), CBD drug type (3), and high THC drug type subdivided into Sativa (11), Hybrid (14), and Indica (10). Ten microsatellites targeting neutral non-coding regions were used. Clustering and genetic distance analyses support a division between hemp and drug type Cannabis. All hemp samples clustered genetically, but no clear distinction of Sativa, Hybrid, and Indica subcategories within retail marijuana samples was found. Interestingly, the two analyzed “research grade marijuana” samples obtained from NIDA were genetically distinct from most drug type Cannabis available from retail dispensaries. Although the sample size was small, “research grade marijuana” provided for research is genetically distinct from most retail drug type Cannabis that patients and patrons are consuming.